Parents, participation, partnership: Problematising New Zealand early childhood education. (September 2016) - Chan, Angel; Ritchie, Jenny
This article interrogates notions of teacher 'partnership with parents' within early childhood care and education settings in the context of Aotearoa (New Zealand). Te Whāriki, the New Zealand early childhood curriculum, clearly positions children's learning and development as being fostered when their families' cultures and practices are recognised. Yet findings from both national evaluative reports and recent studies indicate that, in many instances, families that are not members of the dominant cultural group do not experience this synergy. The authors draw on some recent national evaluative reports to paint a broad picture of the implementation of 'partnership', and then employ illustrative data from several research projects regarding the inclusion of Māori and Chinese families respectively. The authors apply hybridity theory, along with the related idea of funds of knowledge, to reinforce the need for teachers to proactively move beyond the hegemonic safe zones of traditional teacher-dominated practices towards opening up spaces of dialogic, fluid engagement with families whose backgrounds differ from their own. This aspect of teachers' professional responsibility is particularly important in the current era of increasing superdiversity.